The comparison of effects of balneotherapy, water-based and land-based exercises on disease activity, symptoms, sleep quality, quality of life and serum sclerostin level in patients with ankylosing spondylitis: A prospective, randomized study - Ersin Bestaş,; Ümit Dündar,; Tülay Köken,; Buğra Koca,; Hilal Yeşil, (Archives of Rheumatology, 2022)
Objectives: This study aims to compare the effects of balneotherapy, water-based exercise (WBE), and land-based exercise (LBE) on disease activity, symptoms, sleep quality, quality of life, and serum sclerostin level (SSL) in patients with ankylosing spondylitis (AS). Patients and methods: Between January 2019 and January 2020, a total of 60 patients (35 males, 25 females; mean age: 40.9±11.2 years; range, 18 to 55 years) who were diagnosed with AS were randomly divided into the balneotherapy (n=20), WBE (n=20), and LBE (n=20) groups (20 sessions of treatment in groups of five to six patients). The patients were evaluated before treatment and at 4 and 12 weeks using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI), Ankylosing Spondylitis Disease Activity Score-C-reactive protein (ASDAS-CRP), Maastricht Ankylosing Spondylitis Enthesitis Score (MASES), Ankylosing Spondylitis Quality of Life (ASQoL) Scale, Fatigue Severity Scale (FSS), and Pittsburg Sleep Quality Index (PSQI), and SSL were measured. Results: Statistically significant improvements in the BASDAI, BASFI, MASES, BASMI, ASQoL, FSS, and ASDAS-CRP scores were observed in all groups at 4 and 12 weeks of follow-up (p<0.05). A significant improvement in sleep latency was seen in the balneotherapy and WBE groups. Changes in SSL were not statistically significant in any group (p>0.05). Conclusion: Balneotherapy, WBE, and LBE are effective in the treatment of AS, and the beneficial effects may last for at least 12 weeks.